Prevalence of Barrett's Esophagus in Female Patients With Scleroderma. (7th March 2021) - Snyder, Diana L.; Crowell, Michael D.; Kahn, Allon; Griffing, W. Leroy; Umar, Sarah; Ramirez, Francisco C.
Abstract : INTRODUCTION: Systemic sclerosis or scleroderma (SSc) is a chronic autoimmune disease that renders the esophagus prone to significant gastroesophageal reflux due to impaired esophageal clearance and reduced lower esophageal sphincter pressure. The reported prevalence of Barrett's esophagus (BE) in women with SSc varies from 2% to 37% and is derived from older studies with small sample sizes. We aimed to assess the prevalence of BE in a large cohort of women with SSc. METHODS: Women with SSc referred from the Mayo Clinic Arizona Rheumatology Clinic who completed esophagogastroduodenoscopy between 2002 and 2020 were included. Demographic and high-resolution manometry data were evaluated. The diagnosis of scleroderma was confirmed by an expert rheumatologist. The BE diagnosis was confirmed by an expert gastrointestinal pathologist. RESULTS: There were 235 women with SSc who underwent EGD. High-resolution manometry (HRM) was completed in 172 patients. Women with SSc with BE were significantly more likely to have scleroderma esophagus (absent contractility with hypotensive lower esophageal sphincter) on HRM than women with SSc without BE ( P = 0.018). There were 30 patients with SSc (12.8%) with histologically proven BE. Dysplasia was found in 13 (43.3%): 4 with indefinite, 7 with low grade, and 2 with adenocarcinoma. The incidence of any dysplasia was 5.3% per year (0.9% per year for adenocarcinoma). DISCUSSION: This the largest study on prevalence of BE in women with SSc, yielding a prevalence of 12.8%. Women with SSc with BE were significantly more likely to have absent contractility with hypotensive lower esophageal sphincter findings on HRM. The high prevalence and incidence of dysplasia found suggest that women with SSc should be included in the screening recommendations for BE.